PREPARATION AND CHARACTERIZATION OF STAVUDINE ENTRAPPED LIPOSPHERES - Ranjita Shegokar; Kamalinder Singh (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2012)
Lipospheres of stavudine were prepared by melt dispersion technique using trimyristin, tripalmitin and triastearin, stearic acid, Compritol® 888 ATO and Precirol® ATO 5 as lipid matrix in the various drug-lipid ratios. Drug entrapped free flowing solid lipospheres of triglycerides and glyceryl behenate were characterized for surface morphology, particle size distribution, encapsulation efficiency, and in vitrorelease behavior. The effect of drug lipid ratio, the surfactant used, concentration of stabilizer, and stirring speed were identified as the key variables affecting the formation of discrete spherical lipospheres and sustained drug release rate. The lipospheres production conditions were optimized by using 2% w/w sodium cholate and 1% Plural oleic as a stabilizer. The concentration of lipid used had pronounced effect on particle size of the lipospheres. The incorporation efficiency was found to be in range of 30 to 50%. Increase in concentration of surfactant and stirring speed produced fine spherical, smooth, and round lipospheres. All the prepared lipospheres exhibited slow release profiles dictating the Higuchi mode of release.Key words: Lipospheres, stavudine, lipid matrix, hydrophilic surfactant, drug release